Physicochemical Profiles of Goat Meat: Influence of Unsaturated Fatty Acid Enriched Diets - Sondakh, Erwin Hubert Barton; Kalele, Jerry; Waani, Merci; Lapian, Hapri; Sompie, Meity; Ratulangi, Friets (Buletin Peternakan, 2025)
The aim of this research was to determine the physicochemical profiles of meat from goat given a diet containing unsaturated fatty acids. The material used in this research was local male goats aged ± 12 months. Treatment used in the present study was R0, as a control diet, R1: R0 added with 2.5% of tuna fish oil (TFO), R2: R0 added with 5% of tuna fish oil (TFO), R3: R0 added with 2.5% of soybean oil (SO) and treatment R4: R0 added with 5% of soybean oil (SO). This research was conducted for three months. After the feeding trial, the goats were slaughtered, and the quality of the longissimus dorsi was analyzed. The research design used was a completely random design and four replications. The results showed that the feed containing TFO and SO at a level of 2.5% - 5% did not cause a significant difference (p>0.05) in the carcass components and the physical quality of the meat. Meanwhile, other parameters such as meat cholesterol, stearic acid, oleic acid, and linoleic acid were affected significantly (p<0.05). It should be concluded that the giving 2.5% - 5% of feed containing an unsaturated fatty acids profile (tuna fish oil and soybean oil) has not shown changes in the physicochemical quality of meat. But at the level of tuna oil and soybean oil, up to 5% of dry matter are able to increase the unsaturated fatty acid profile in meat.